Improving of Platform Train Interface (PTI) Safety Based on Platform Screen Door (PSD) Technology at (KTM Serdang and LRT Terminal Bersepadu Selatan) - Nordin, Hasdino; Prasetijo, Joewono; Saruji, Shazrul (Progress in Engineering Application and Technology, 2022)
The goal of this research is to give background information on platform-train-interface (PTI) safety as well as examples of best practices. First of all, the Platform Train Interface (PTI) are the boundary between the platform and the train (or track if no train is present). The platform train interface safety issues have been much disputed due to accident occur in the past 10 years. Common accidents happen such as slips, trips and falls while getting on and off, people can be trapped in the train doors and dragged along, fall onto the track and be struck by the train. Passengers may be injured if they fall through a gap between the train and the platform. The effects of such catastrophes are frequently devastating. In order to increasing and maximizing the safety passenger at platform, Platform screen door technology have been applying at the platform. Platform screen doors (PSD) are the sliding barrier doors installed at the edges of station platforms in many modern metro stations and occasionally on heavy rail systems. This system serves many functions among which are the suicide prevention, optimization of station energy consumption and safety, particularly by shielding passengers from gaining access to the rail tracks. PSD can prolong dwell time, increase the danger of mantrap and can extend emergency evacuation periods, among others. These pave ways for the existence of PSD to have both positive and negative effects on the railway system. This study would have expected result base on the identified the benefits that could be derived from installing PSD at train stations and the safety systems that have been apply in order to enhanced safety, improved reliability and punctuality, more convenience and increase in attractiveness of the station.